PRIMARY SCHOOL EDUCATION IN MADAGASCAR UNDER CONDITIONS OF POVERTY AND RURAL INEQUALITY - Soameva Léa; Koto Bernard; Marolahy Jacquot Urbain (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
This study aims to examine primary school education in Madagascar under conditions of poverty and rural inequality, with particular attention to how structural deprivation shapes educational access, learning readiness, and school quality at the primary level. The research explores the interconnected roles of household economic conditions, school infrastructure, teacher capacity, community engagement, and institutional management in shaping educational experiences in rural settings. Qualitative research design was employed to capture the perspectives and lived experiences of key educational stakeholders. Data were collected in the Atsimo Andrefana Region of Madagascar, specifically within the CISCO of Toliara II, Sakaraha, and Morombe, areas characterized by limited resources and predominantly rural populations. Primary data consisted of semi-structured interviews with 35 key informants, focus group discussions, and document analysis involving teachers, school principals, parents, community members, and local education officials. The findings reveal that poverty-related challenges, including malnutrition, livelihood insecurity, inadequate school infrastructure, and uneven professional support for teachers, significantly undermine learning readiness and instructional quality. Educational inequality is further reinforced by weak school management capacity and limited access to technological and administrative resources. Community involvement and culturally responsive teaching practices were found to partially mitigate these constraints by enhancing student engagement and school resilience. The study concludes that improving primary education in rural Madagascar requires integrated and context-sensitive strategies linking education policy with social protection, targeted investment in rural schools, continuous teacher professional development, and strengthened community–school partnerships to promote more equitable educational outcomes.